0896 Nutritional Status Improves Following The Implementation Of Positive Airway Pressure For The Treatment Of Obstructive Sleep Apnea In Youth With Down Syndrome. (27th May 2020) - Arputhan, A; Xanthopoulos, M S; Tapia, I E; Hernandez, P; Kelly, A
Abstract: Introduction: In typically developing youth, increases in body mass index (BMI) and rates of obesity accompany treatment of obstructive sleep apnea syndrome (OSAS) with adenotonsillectomy regardless of baseline BMI and OSAS severity. Residual OSAS following adenotonsillectomy and overweight/obesity are common in Down syndrome (DS). We sought to examine the impact of positive airway pressure (PAP) on BMIZ in youth with DS and OSAS. Methods: Baseline, 6, and 12 month height/length and weight as well as pre-PAP PSG data were abstracted from the Children's Hospital of Philadelphia Sleep Center for patients with DS and OSAS initiated on PAP between 01/01/2014-07/11/01/2017 (N=73; Median age=6.6y IQR: 3.6-12.1; 52% White, 29% Black; 42% Male). BMIZ was calculated. Longitudinal mixed effects models adjusted for adherence from 0-6 months, baseline BMIZ, and baseline SpO2 nadir were used to evaluate change in BMIZ at months 6 and 12 and the impact of baseline BMIZ on trajectories. Results: OAHI (median; IQR) at initiation was 15.9 (8.1-28.9) events/hour, SpO2 nadir was 83% (77-88), and BMIZ was 1.50 (0.94-2.34). No differences in BMIZ at 6 and 12 months compared to baseline BMIZ were found (p>0.2 for both). Baseline BMIZ was associated with BMIZ at 6- and 12 months (β-coefficient=0.99; p<0.0001); the increase in BMIZ at 12 mo (β-coefficient= 0.49, p=0.001) was offset with decreasing BMIZ (12mo*baseline BMIZ β-coefficient= -0.3; p<0.0001); such that lower BMIZ was associated with increases in BMIZ while higher BMIZ was associated with decreases in BMIZ. Conclusion: Initiation of PAP has a beneficial impact on nutritional status in youth with DS and OSAS. In youth who are at the lower end of BMIZ, BMIZ increases to a healthier status following the initiation of PAP, and in youth who are at the higher side of BMIZ, BMIZ decreases to a healthier status. Prospective studies are needed to elaborate on these associations. Support: None